Investigating the transfer of techniques for electronic technical support documentation from aerospace to machine tools - Greenough, Richard M.; Williams, David (Springer Science Business Media, 2007)
Abstract This paper describes a scoping study that investigated the possible transfer of techniques for creation of electronic technical support documentation from the aerospace industry to the machine tool industry. Electronic maintenance manuals have been supplied by aircraft manufacturers over the past 20 years with demonstrated benefits. Despite research that indicates the likelihood of similar benefits for machine tool users, the supply of electronic technical support documentation (TSD) by machine tool manufacturers is rare, and the techniques for the creation of TSD are inefficient. This paper describes the relevant trends affecting the machine tool industry and the background of the use of electronic TSD in aerospace. Data was collected via interviews with technical authors, document users and software suppliers from both industry sectors, as well as a questionnaire and a workshop. The results were analysed to form a view of the potential for technology transfer over the next 5 years.
Keywords: Technical documentation; Aerospace industry; Machine tools; Maintenance